(untitled) (Medico Legal Update, 2019)
In Indian society marriage is considered sacrosanct and essential for procreation and propagation of humanity. The sizable numbers of deaths in female are unnatural. In young married women more often they are associated with demands of dowry or harassment & cruelty by husband or in-laws. Present autopsy based study was conducted to study the socio-demographic pattern and reasons behind unnatural deaths in newly married females. Females living in Hindu joint family structure from lower socioeconomic strata have shown increased incidence of unnatural death, predominantly during early years of their marriage. The most common incident resulting in unnatural death was vehicular accident injuries (37.14%), followed by Hanging (20%), Strangulation (17%) and Poisoning (14%). Accidental deaths were most frequent comprising 40% of total cases, followed by suicides comprising 37.14% and homicides had a share of 22.86%. Significantly in 20% cases there was allegation of dowry demand/torture/harassment by in-laws/husband of the deceased and most of them were homicides, killed either by strangulation or burning.